MASALAH KESEJAHTERAAN SOSIAL DAN PEKERJAAN SOSIAL DI INDONESIA: KECENDERUNGAN DAN ISU - Edi Suharto (Sosio Informa, 2004)
Social Welfare Problems and Social Work in Indonesia: Trends and Issues.The argument that social work is a human profession dealing with social problems is severalhundred years old. However, as social work in indonesia is still searching for its original identity., they discussion whether social work should focus on a narrow or broader scope of social problems has been a hotly debate, perhaps since the profession born in the country more than four decades ago. This paper takes the position that social workers should be able to respond to social problems. However, in order to have a clear demarcation of professional intervention, social workers in Indonesia need to focus their expertise on dealing with social problems in narrow sense, or in what this paper calls 'social welfare problems'. This paper than goes on to highlight the 'big four' problems, such as poverty and destitution, disability neglect, and inadequate housing and discuss the implication for social work education. By knowing the nature of social welfare problems to be addressed, it is argued that social workers competencies can be identified and curriculum contents for social work education can be developed.Â